The potential use of N-methyl-3, 4-methylenedioxyamphetamine (MDMA) assisted psychotherapy in the treatment of eating disorders comorbid with PTSD. (January 2021) - Brewerton, Timothy D.; Lafrance, Adele; Mithoefer, Michael C.
Abstract: Despite advances in the field, eating disorders (EDs) remain very challenging disorders to treat, especially when comorbid with posttraumatic stress disorder (PTSD). N-methyl-3, 4-methylenedioxyamphetamine (MDMA)-assisted psychotherapy for treatment refractory PTSD shows great promise, with two-thirds of participants achieving full remission at 1 year or more at follow-up. PTSD is a common comorbidity associated with EDs, and patients with EDs and PTSD (ED-PTSD) are reported to have higher severities of illness, greater comorbidities, higher treatment dropouts, and poorer outcomes. We hypothesize that MDMA-assisted psychotherapy will be efficacious in the ED-PTSD population for both ED and PTSD symptoms. The rationales for and proposed mechanisms of MDMA-assisted psychotherapy for ED-PTSD are considered from neurobiological, psychological and social perspectives. MDMA is associated with unique psychopharmacological effects, including: 1) reduced fear, 2) enhanced wellbeing, 3) increased sociability/extroversion, 4) reduced self-criticism, 5) increased compassion for self/others, 6) increased interpersonal trust, and 7) alert state of consciousness. These anxiolytic and prosocial effects may counteract avoidance and hyperarousal in the context of psychotherapy for those with ED-PTSD. Other clinical features of EDs that may be amenable to MDMA-assisted psychotherapy include body image distortion, cognitive rigidity, and socio-emotional processing difficulties. To illustrate its potential, personal accounts of individuals with ED-PTSD symptoms reporting benefit from MDMA adjunctive to psychotherapy are described. In addition, the possible risks and challenges in conducting this work are addressed, and future implications of this proposal are discussed.